The Relationship between Celebrity Worship and Psychological Well-Being in Students of the Faculty of Psychology, Universitas Negeri Malang - Salsabila, Alwiyah; Eva, Nur; Nugrahani, Rizka Fibria (Universitas Negeri Malang, 2024)
This research is based on the fact that most students at the Faculty of Psychology, Universitas Negeri Malang, still have moderate and low levels of psychological well-being. Students, in this case, should be more focused on how they achieve an optimal level of psychological well-being, but there are still early adult individuals who have celebrity worship. When early adult individuals have celebrity worship, it will have a negative impact, such as anxiety, stress, and even depression, which leads to decreased psychological well-being. This research aimed to determine the description of celebrity worship and psychological well-being and the relationship between the two variables in the Faculty of Psychology, Universitas Negeri Malang students. Research data were collected using the short version of the Celebrity Attitude Scale (CAS) and Ryff's Psychological Well-Being (RPWB) Scale. The correlation coefficient value of the two variables is -.012, with a significance value of .878. The results stated an insignificant relationship with a negative correlation between celebrity worship and psychological well-being in students of the Faculty of Psychology, Universitas Negeri Malang.